Orienting Flood Risk Management to Disaster Risk Creation: lessons from the Water Framework Directive - Giacomo Cazzola (Fondazione Eni Enrico Mattei (FEEM), 2022)
This paper proposes an application of the analytical path assembled within my PhD research on Disaster Risk Creation (DRC) in humanitarian contexts, to Flood Risk Management (FRM) planning in Italy. The investigation concerns some key challenges, for spatial planning and disaster risk management, in understanding, evaluating, and addressing Disaster Risk (DR) drivers and pressures, those processes and land uses enhancing exposure, vulnerability and flood hazard itself. The reference methodological approach benefits from well-established theoretical models of causal analysis of Disaster Risk Creation processes as bridging analytical construct for reordering and coordinating flood risk management interventions. These theoretical and analytical reflections are build upon a gap between the European Water Framework and the Flood Directives that, despite their many interconnections and commonalities, differ in the focus (or lack of) on underlying causal factors. Thus, the Water Framework Directive provides a valuable operational reference for orienting flood risk management planning to the reduction of disaster risk creation components.
Keywords: Q54; R58; 330; Flood Risk Management; European Flood Directive; Risk Driver; Spatial Planning